Comparison of the effects of enamel matrix derivative and mineral trioxide aggregate on the mineralization potential of human cementum-derived cells - Hyunsook Chung; Wonkyung Yang; Miri Kim; Hyunjung Ko (Elsevier, 2011)
Background/purpose: Cementogenesis is a critical event in the repair of endodontic perforations and the enamel matrix derivative (EMD) was reported to induce cementogenesis when used in periodontal disease. Yet, there is no study investigating the effects of EMD compared with mineral trioxide aggregate (MTA), a well-known material used for perforation repair. Because cementoblasts play important roles in the repair and regeneration of cementum, the aim of this study was to investigate the effect of EMD on the mineralizing potential of human cementum-derived cells (HCDCs). Materials and methods: HCDCs were cultured as previously described. ProRoot MTA was mixed and placed on the bottom of 6-well tissue culture plate inserts under aseptic conditions. These were allowed to set for 24 hours in a humidified incubator at 37°C. Cells were seeded onto culture plates at an initial density of 5000 cells/cm2 and were treated with either MTA or EMD. Cells with only culture medium were used as the control. Levels of osteopontin and matrix metalloproteinase-13 were assessed by an enzyme-linked immunosorbent assay with supernatants of the culture media collected on Days 3 and 6 of incubation. Mineralization was detected on Day 6 by Alizarin red staining of cells. Results: Concentrations of osteopontin in the EMD group were significantly higher (P < 0.05) than those in the control group at all time points. On both Days 3 and 6, there was an increase in matrix metalloproteinase-13 expression in the EMD group compared with the control group, but the difference was significant only on Day 6 (P < 0.05). Conclusions: Compared with MTA, EMD significantly stimulated the mineralization potential of HCDCs, which implies the potential of EMD for use as an endodontic repair material.